What's Up Omni? The Relationship Between Omni-Channel Supply Chain and Logistics Service Quality In Influencing Online Purchasing Behaviour - Emy Ezura A-Jalil; Jing Foo Yee; Wan Salmuni Wan Mustaffa (International Journal of Supply Chain Management, 2020)
Consumer behavior had been affected by the evolution of digital technologies and the internet. Online shopping is becoming more popular, with e-commerce market growth that encourages the involvement of retailers. However, consumers' satisfaction is still the same as they request for a seamless and frictionless shopping experience, an 'Omni-channel supply chain.' Retailers need to understand the new phenomenon and how the concept is influencing customer purchasing behavior, especially online shopping. Several types of research had highlighted the importance of logistics service quality in predicting online purchasing behavior. Thus, this study investigates the relationship between the Omni-channel supply chain and logistics service quality in influencing online purchasing behavior. A survey-based approach is used to collect data from consumers about their perceptions. Overall, the study had enhanced the understanding of the relationship between the Omni-channel supply chain and logistics service quality with online purchasing behavior. Besides, the knowledge of online purchasing behavior in the Omni-channel context has enabled a retailer to allocate resources in designing new strategies.